تقييم الأداء المالي والبشري للمؤسسة االقتصادية دراسة حالة مؤسسة نفطال - الوادي - ايوب نصري; مرزوق محمد الصديق; نوبلي الطاهر (جامعة الوادي University of Eloued, 2025)
"تسعى المؤسسات االقتصادية إلى تحقيق أداء متكامل يجمع بين الكفاءة المالية والفعالية البشرية، لما له من دور محوري في تحقيق الأهداف ا لاستراتيجية وضمان الاستدامة. تهدف هذه الدراسة إلى تحليل العلاقة بين كفاءة الأداء المالي وكفاءة الأداء البشري داخل المؤسسات الاقتصادية، من خلال دراسة ميدانية على وحدة نفطال بولاية الوادي، ومعرفة مدى تأثير أحدهما على الآخر. حيث أكدت النتائج وجود عالقة إيجابية وذات دلالة إحصائية بين كفاءة الأداء البشري وتحسين المؤشرات المالية، تبين أن حافز العاملين تكوينهم ينعكس إيجاب على الإنتاجية و الربحية، كما أظهرت الدراسة قصورا في ربط الأداء المالي بموارد البشرية، واعتماد المؤسسة على مؤشرات تقليدية في التقييم. أوصت الدراسة باعتماد نموذج تقييم تكاملي يشمل البعدين المالي والبشري، وتعزيز الاستثمار في رأس المال البشري "Economic institutions strive to achieve integrated performance that combines financial efficiency and human effectiveness, given their pivotal role in achieving strategic objectives and ensuring sustainability. This study aims to analyze the relationship between financial performance efficiency and human performance efficiency within economic institutions, through a field study of the Naftal unit in El Oued Province, and to determine the extent to which one influences the other. The results confirmed a positive and statistically significant relationship between human performance efficiency and improved financial indicators. It was shown that employee motivation and training positively impact productivity and profitability. The study also revealed shortcomings in linking financial performance to human resources, and that organizations rely on traditional evaluation indicators. The study recommended adopting an integrated evaluation model that encompasses both financial and human dimensions, and enhancing investment in human capital. The study recommended adopting an integrated evaluation model that includes both financial and human dimensions, and enhancing investment in human capital
ماسترالعلوم الإقتصادية
Keywords: أداء مالي; أداء بشري; كفاءة; مؤسسة اقتصادية; نفطال; تقييم الأداء; رأس المال البشري; financial performance; human performance; efficiency; economic institution; Naftal; performance evaluation; human capital.